EXAMINATION FOR TYPHOID FEVER USING IMMUNO MAGNETIC BEADS INHIBITION (TUBEX TF) METHOD AT RSUD SITI FATIMAH SOUTH SUMATERA PROVINCE 2024 - Meilani, Selly Asti (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Background: Typhoid fever was a systemic infectious disease caused by the Salmonella typhi bacteria. The symptoms included increased body temperature, headache, nausea, loss of appetite, weakness, diarrhea, liver and spleen damege and death. Usually occurs within 1 to 3 weeks after exposured to Salmonella typhi bacteria. Aims: This research aimed to find out how to check for typhoid fever using the Immuno Magnetic Beads Inhibition (Tubex TF) method at RSUD Siti Fatimah South Sumatra Province in 2024. Methods: The methodology used in this research was quantitative descriptive with a research sample of 4 serum samples from patients with suspected typhoid fever collected by purposive sampling. The results: The results showed one possitve sample with a score of 4 on Tubex TF and three negative samples with a score 2 on Tubex TF. Conclusion: This showed that the Tubex TF method can differentiate the severity of thyphoid fever effectively.